Penerapan Model Pembelajaran Simulasi untuk Meningkatkan Kemampuan Menghafal Kosakata Bahasa Arab Terhadap Siswi Pesantren Hidayatullah Bungadidi Luwu Utara - Haderana; Adriani; Felany Fitriani; Nanda Amelia; Narsi (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to determine the effectiveness of the application of the simulation learning model in improving the ability to memorize Arabic vocabulary (mufradāt) in female students at the Hidayatullah Bungadidi Islamic Boarding School, North Luwu. The study used the Classroom Action Research (CAR) method which was implemented in two cycles, with each cycle including the planning stage, action implementation, observation, and reflection. The research subjects consisted of 20 female students. Data collection techniques were carried out through observation, tests, and documentation. Data analysis used quantitative and qualitative descriptive techniques. Test data were analyzed by calculating the average value and percentage of learning completion, while observation data were analyzed to determine the activities and involvement of female students during learning. The results of the study showed a significant increase in the ability to memorize Arabic vocabulary (mufrodat) in each cycle. In the pre-cycle stage, only 2 female students (10%) achieved learning completion. In the first cycle, this increased to 11 female students (55%), and in the second cycle it reached 19 female students (95%). These findings indicate that the simulation learning model is able to create an active, interesting, and effective learning atmosphere in helping female students understand and remember Arabic vocabulary